Has the DSM Failed? - Sumit Anand (Current Practice in Medical Science Vol. 9, 2022)
The DSM’s atheoretical and consensus-driven diagnostic classification system has become increasingly problematic to implement into clinical practice, by creating diagnostic confusion between diagnoses. . Neither has it properly incorporated decades of research on etiology, in order to inform diagnostic clarity. Instead it instructs clinicians to use algorithmic/iterative methods of making diagnoses, contrary to longstanding clinical training traditions.., Academic institutions in the United States are now mostly reliant on the DSM. making it a paradoxical impediment to the authentic understanding of psychiatric disorders as well as their treatments.